Study Of Regional Development Planning Index Of Serang Regency 2023 - Lukman Hakim, Agus; Maulana, Rachmat; Sanjaya, Natta; Hanifah, Hanifah; Yuniar, Siti (Indonesian Journal of Social Science Research, 2024)
This research aims to measure the Serang Regency Regional Development Planning Index. In order to realize the ideals and goals of the nation as stated in the Preamble to the 1945 Constitution, namely achieving a just and prosperous society, both the central and regional governments need to develop strategies to create development both regionally and in terms of human resources within it. As a concrete step to ensure that development activities are effective, efficient and targeted, a national development plan is needed that is formed in a system. Regional Development Planning Index Measurement Components which include: a) Synergy, b) Quality of Planning, c) Linkage of Development Planning with Performance Planning, which consists of 6 aspects, 22 indicators and 40 sub-indicators. In calculating the IKP for Serang Regency, the measurement method carried out by Bappenas is used by assessing the results of planning documents that have been prepared by the Regional Government within a period of one year before the measurement year. The results of the measurements carried out became a reference for improving the quality of regional government planning documents. Based on the results of a documentation study examination of Serang Regency regional planning documents, it was found that the results of the Synergy dimension had an assessment score of 25.75 from a maximum weight value of 32. The value obtained from the Planning Quality dimension was 56 from a maximum weighted score of 58. The relationship between Development Planning and Performance Planning The assessment results were obtained at 10 out of a maximum weighted score of 10